The Regulation of Shariah for Electronic Media Broadcasting - Anwar Farooqi, Noor; Bin Daud, Mahyuddin; Naqib Eishan Jan, Mohammad (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
Abstract Islam is a blessed religion that strongly regulates and supports the fundamental rights and freedom of human beings. The role of electronic media in every society is a certain fact. A society cannot progress well until the foundation of the means of communication is not strong and stable. Even in our country, where 99% of the people are Muslims, all electronic media should prepare their broadcasts with the provisions of Sharia because electronic media plays a very effective role in building a society. According to the regulation of Sharia, electronic media has a responsibility to try not to broadcast what is not useful for society and harms the society, and never be negligent in this regard, because a moment of negligence in the media field destroys the society. The purpose of this paper is to examine in detail the regulatory principles of electronic media broadcasts within the framework of Sharia. Therefore, if the electronic media takes into account the rules of Sharia in their broadcasts, then two important goals will be achieved. Firstly, the scope of Da’wah will expand and many people will accept Islam, secondly, the propaganda that the Western media is doing against Islam will be weakened and eventually destroyed. The method of the research is explanatory, analytical, and descriptive. This study is done under the theory and library-based. The related issues and criteria will be described and analyzed from first-hand resources namely the Quran and Hadith. If the relevant information is not found in first-hand sources, then the books, articles, newspapers, journals and internet sites will be used. This article is very valuable because it can be used to strengthen the legal system of Afghanistan. Also, the media and journalists who broadcast in Islamic countries will be prevented from media violations by reading and observing this article, which will result in a beautiful world and the hereafter. In addition to this, any credibility that the journalism profession has lost today will be restored.